Amelioration of capillary regression and atrophy of the soleus muscle in hindlimb‐unloaded rats by astaxanthin supplementation and intermittent loading. Issue 8 (20th June 2014) - Kanazashi, Miho; Tanaka, Masayuki; Murakami, Shinichiro; Kondo, Hiroyo; Nagatomo, Fumiko; Ishihara, Akihiko; Roy, Roland R.; Fujino, Hidemi
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? We asked whether the combination of astaxanthin supplementation and intermittent loading would attenuate both the muscle atrophy and the capillary regression associated with chronic unloading. What is the main finding and its importance? Intermittent loading alone attenuated atrophy of the soleus, while astaxanthin treatment alone maintained the capillary network in the soleus. The combination of these two interventions ameliorated both the muscle atrophy and the capillary regression induced by chronic unloading. A chronic decrease in neuromuscular activity (activation and/or loading) results in muscle atrophy and capillary regression that are due, in part, to the overproduction of reactive oxygen species. We have reported that antioxidant treatment with astaxanthin attenuates the overexpression of reactive oxygen species in atrophied muscles that, in turn, ameliorates capillary regression in hindlimb‐unloaded rats. Astaxanthin supplementation, however, had little effect on muscle mass and fibre cross‐sectional area. In contrast, intermittent loading of the hindlimbs of hindlimb‐unloaded rats ameliorates muscle atrophy. Therefore, we hypothesized that the combination of astaxanthin supplementation and intermittent loading would attenuate both muscle atrophy and capillary regression during hindlimb unloading. As expected, 2 weeks of hindlimb unloading resulted in atrophy, a decrease in capillary volume and a shift towards smaller‐diameter capillaries in the soleus muscle. Intermittent loading alone (1 h of cage ambulation per day) attenuated atrophy of the soleus, while astaxanthin treatment alone maintained the capillary network to near control levels. The combination of intermittent loading and astaxanthin treatment, however, ameliorated atrophy of the soleus and maintained the capillary volume and luminal diameters and the superoxide dismutase‐1 protein levels near control values. These results indicate that intermittent loading combined with astaxanthin supplementation could be an effective therapy for both the muscle atrophy and the capillary regression associated with a chronic decrease in neuromuscular activity.